Gas-pressure tunable photon-pair generation in a suspended core fiber - Hammer, Jonas; Chekhova, Maria; Russell, Philip St. John; Joly, Nicolas (Frontiers in Optics - Proceedings Frontiers in Optics + Laser Science APS/DLS, 2019)
Four-wave-mixing in a suspended core fiber is spectrally tuned by filling the fiber with argon. This allows the generation of photon pairs to be tuned over at least 40 nm, extendible using even higher pressures.
CRIS-Team Scopus Importer:2021-04-20